Emotional labour profiles: associations with key predictors and outcomes - Fouquereau, Evelyne; Morin, Alexandre J.S.; Lapointe, Émilie; Mokounkolo, René; Gillet, Nicolas (Taylor & Francis (Routledge), 2018)
The present study examines how three emotional labor strategies (hiding feelings, faking emotions, and deep acting) combine within different profiles of workers among two samples characterized by different types and intensity of customer contact. In addition, this research investigates the role of perceived workload as well as perceived organizational support, supervisor support, and colleagues support in the prediction of profile membership. Finally, this research also documents the relation between emotional labor profiles and adaptive and maladaptive work outcomes (job satisfaction, work performance, emotional exhaustion, sleeping problems, psychological detachment, and counterproductive work behaviors). Latent profile analysis revealed three similar emotional labor profiles in both samples. Results also showed the most desirable levels on all outcomes to be associated with Profile 3 (Low Emotional Labor/Low Surface Acting and Moderate Deep Acting), followed by Profile 2 (Moderate Emotional Labor/Moderate Surface Acting and High Deep Acting) and Profile 1 (H igh Emotional Labor), with most comparisons being statistically significant in both samples. In contrast, a more diversified pattern of findings was observed in the prediction of profile membership. For instance, perceived colleagues support did not predict membership into any of the profiles, while supervisor support predicted an increased likelihood of membership into Profile 3 relative to Profiles 1 and 2.